Beryllium-7 in lichens (Usnea antarctica Du Rietz) colllected in the Machu Picchu Antarctic Scientific Station during the austral summer 2012-2013 - Osores, José (2013)
The presence of Be-7 in Antarctic lichens is verified with an increase in their levels of concentration, showing an average derived activity 423,13 ± 80,39 Bq/kg for 2013. Because of the good capability of incorporation of Be-7 in Antarctic lichens, they can use these organisms as biomonitors to assess the cosmogenic activity and also use them as tools in the evaluation of geomorphological and sedimentary processes in the region.